Relationship between Husband's Social Support and Participation in Pregnant Women Class in Denpasar City in 2019 - Laksmi, Ni Putu Citra (PT. Riset Press International, 2024)
The Pregnant Women class program is one of the government programs to increase the knowledge of pregnant women about pregnancy, preparation for childbirth, postpartum, newborns, and toddler development so that mothers are expected to be able to identify health problems experienced, but maternal participation in the class of pregnant women is low. The husband's social support is a strengthening factor for mothers to be able to participate in classes for pregnant women. This study aims to see whether there is a relationship between a husband's social support and participation in classes for pregnant women. This study is an observational analytical study with a cross-sectional approach. The sampling technique is non-probability sampling by consecutive sampling of 78 people. This research was conducted from April 1 to May 1, 2019, at the Denpasar City Health Center. The results showed that most of the husband's social support was weak (56%) and mothers did not participate in classes for pregnant women (56%). Statistical tests with the correlation of contingency coefficients obtained ρ = 0.000 value and r value = 0.707, meaning that there is a strong relationship between the husband's social support and participation in pregnant women's classes. The implication of this study is to increase knowledge related to husbands' social support factors that play a role in women's participation in pregnant women's classes.